OCCURRENCE OF TINEA INFECTION WITH COMPARATIVE STUDY OF COMMERCIAL ANTIFUNGAL AND TRADITIONAL HERBS IN DISTRICT SWAT, KHYBER PAKHTUNKHWA, PAKISTAN - UDDIN, MN; KHAN, B; SHAH, M; AHMAD, S; ALI, A; KHAN, T; NIQABULLAH, .; KHAN, S (Biological and Clinical Sciences Research Journal, 2024)
Dermatophytosis, mainly Tinea infections, is caused by more than 30 species of dermatophytes. Tinea infections are usually restricted to superficial skin, but it has the potential for systemic infection, particularly in immune-compromised patients. The use of plant extract against tinea infection is well documented. However, limited studies have been conducted on the comparative studies of commercial antifungal drugs and traditional herbs. Objective: The current study was aimed to pinpoint the prevalence of tinea infection-causing pathogens, a comparative study of commercial antifungal drugs and traditional herbs against two fungal species, Trichophyton rubrum, and Aspergillus fumigatus isolated from dermatophytosis patients in Swat. Methodology: 190 samples were collected from infected peoples’ skin, nails, and hairs in different hospitals and private medical facilities. The samples were cultured on potato dextrose medium, labeled carefully, and incubated. Moreover, the growths were observed under a microscope, and species were identified based on morphological characteristics. Results: A total of 12 different fungal species were isolated. Among all T. rubrum species, 25% was recorded, followed by Candida (19.4%) and Penicillium spp (16.6%). The minimum rate was recorded for Aureobasidium pullulans, Epidermphyton floccosum, Trichophyton basicola, T. verrucosum, T. tonsurans, and T. consultants with 2.78% each. A total of six anti-fungals were examined, and fluconazole and clotrimazole showed the best results against T. rubrum and A. fumigatus. Eight traditional herbs were studied against T. rubrum and A. fumigatus. Ethyl acetate extract showed the best results against both species, followed by methanol extract. n Hexane extract was found to be less effective. Conclusion: The study concluded that fluconazole, clotrimazole, and Ethyl acetate extract of medicinal plants were more effective against T. rubrum and A. fumigatus.